If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(x + -1) = -8(2 + -1x) + 8x Reorder the terms: 16(-1 + x) = -8(2 + -1x) + 8x (-1 * 16 + x * 16) = -8(2 + -1x) + 8x (-16 + 16x) = -8(2 + -1x) + 8x -16 + 16x = (2 * -8 + -1x * -8) + 8x -16 + 16x = (-16 + 8x) + 8x Combine like terms: 8x + 8x = 16x -16 + 16x = -16 + 16x Add '16' to each side of the equation. -16 + 16 + 16x = -16 + 16 + 16x Combine like terms: -16 + 16 = 0 0 + 16x = -16 + 16 + 16x 16x = -16 + 16 + 16x Combine like terms: -16 + 16 = 0 16x = 0 + 16x 16x = 16x Add '-16x' to each side of the equation. 16x + -16x = 16x + -16x Combine like terms: 16x + -16x = 0 0 = 16x + -16x Combine like terms: 16x + -16x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 13.6-3.5t=14.02 | | 2x^2+2y^2+16x-36y+96=0 | | 0.2(x+50)+0.2x=14 | | 1.5q-1.8-4.8q=-4.3q-1.7 | | 5x^2-9x=6 | | -6-(6-4p)= | | -6.1(2p+4)-1.8(4p-6)= | | 9-2[8-(3y-9)]= | | 100[.09(m+8)]= | | (12-x)*(9-x)=0.78 | | (5x-3)+(9x-6)=0 | | 9x^2+9y^2=63 | | -x+27+3x+9=9x-153 | | -x+27+3x+9=x-17 | | 3x^2-18x=-27 | | -5x-2+4x+7=0 | | 5xy-8x-10y=16y | | 20x^2+11x-30=0 | | 25x+6x+4=21x | | 3x+6x^2y^3+4y= | | 36x-24=36x+24 | | (x+-4)(x+-4)=(x+-4)(2x+-1) | | 13x+7(-3x-1)=-68 | | x^2+12x-138=0 | | (x-4)=(x-4)*(2x-1) | | 5+2m-3=7m+2-4m | | -4x^2=16 | | 3y+7=6y-56 | | x+.1=-.8 | | 11x-76=6x-6 | | (x-11)(x-11)=0 | | 4x+2+3x=2+3+2x |